PERSEBARAN LOKASI SMP DAN SMA DALAM UPAYA PENINGKATAN AKSESIBILITAS DAN PELAYANAN SEKOLAH DI KECAMATAN GUNUNGPATI - Sriyanto, Sriyanto (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2015)
Gunungpati District is one of the districts in the city of Semarang, which has developed rapidly. Developmentcontinues, both physical and nonphysical. In education, District Gunungpati have different characteristics with otherdistricts in the city of Semarang. One of them can be seen from the level of Coarse Participation Number (CPN) andPure Partisipation Number (PPN) is very low (less than 100%). These conditions coupled with the presence of school(junior and high school) who distributions not in accordance with the development and distribution of population.Permendiknas No. 24 Year 2007 has set a school was established.The aim of this research are (1) understand thespread of CPN and PPN in the District Gunungpati, (2) availability of educational facilities available. The focus of thisresearch is the spread of CPN and PPN, the distribution patterns or patterns of distribution of school location, servicelevel educational facilities, and the suitability of the location of schools (affordability, distribution patterns, and sitecondition). Subsequently analyzed using descriptive analysis, service level, spatial analysis and spatial analysis(nearest-neighbor index). The results showed that the level CPN and PPN, both junior and senior high schools inDistrict Gunungpati in the year 2014 less than 100%. Judging from the condition of the tread, the utilization of theenvironment around the school remained largely in the form of vacant land, mixed forest and plantations. So it is stillpossible to do development. In fisografis, location of schools are on a flat area with a level of natural hazards(landslides and floods) is relatively low.